Breast Reconstruction after Mastectomy in Women with Breast Cancer: A Systematic and Meta-Analysis Review - Anbiyaiee, Amir (World J Plast Surg, 2020)
BACKGROUND: Immediate Breast Reconstruction (IBR) is an additional surgical procedure that may increase postoperative complications (such as flap necrosis, infection, and hematoma) and delay the initial time for adjuvant chemotherapy in some patients. In this systematic and meta-analysis, we provide overall survival rates of patients who underwent mastectomy with and without IBR. METHODS: The following databases were systematically searched between 2015 to 2019 without language restrictions in PUBMED, EMBASE, Web of Science, and Cochrane Library. In addition, the relevant references in the list of all included articles were also checked. The search term included “breast cancer” and “breast reconstruction” “mastectomy”. RESULTS: The sample size was a range from 339 to 5644 patients. The median age was 46.3 years. The results showed no significant differences in terms of overall survival between two groups. CONCLUSION: The results showed that IBR after mastectomy did not affect the overall survival.